Effects of low-frequency noise on human cognitive performances in laboratory. Issue 1 (March 2018) - Rossi, Laura; Prato, Andrea; Lesina, Lorenzo; Schiavi, Alessandro
Indoor working and living environments are increasingly exposed to low-frequency noise sources. The well-known relationship between noise conditions and effects on human health requires the development of a proper procedure to evaluate the stress due to acoustical factors. For this purpose, an experiment, based on Soft Metrology principles, was designed to measure the changes of cognitive and physiological parameters (response time and heart rate) on a sample of 25 male and female volunteers, aged 19–29 years, exposed to three types of noise in a hemi-anechoic room. Participants were involved in a cognitive task (Stroop effect) for 10 min in four different conditions: silence, stochastic broadband multi-tonal noise (BBN), stochastic low-frequency multi-tonal noise (LFN1), and low-frequency stationary noise with regular amplitude modulation (LFN2). All sounds were reproduced by two loudspeakers at equivalent sound pressure level of 93 dB. Results showed that in noise conditions, subjects reduced their response times. This is an evidence of growing stress, according to arousal theory. In particular, LFN1 and LFN2 produced cognitive stress comparable to stochastic broadband multi-tonal noise. Furthermore, subdividing the subjects in extroverts and introverts through the Eysenck Personality Questionnaire–Revised psychological test, it was shown that LFN1 and LFN2 produced higher stress effects than stochastic broadband multi-tonal noise on the cognitive performances and a physiological stress comparable to stochastic broadband multi-tonal noise in introverts, whereas no effects were observed in extroverts, as hypothesized by Eysenck. This result highlights the necessity in the future to consider the personality parameter as a key factor in the evaluation of the effects of noise on humans.